1993
DOI: 10.1002/polb.1993.090311118
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical processes in aromatic polyimides. Studies with model compounds

Abstract: Emission mechanism in an aromatic polyimide, PI(BPDA/PDA), derived from biphenyltetracarboxylic dianhydride and p‐phenylene diamine were studied with ultraviolet visible absorption and fluorescence spectra of a series of the model compounds. The excitation spectrum of the intermolecular charge‐transfer (CT) fluorescence peaking around 550 nm of PI(BPDA/PDA) thin film was completely consistent with the absorption spectrum, indicating that the intermolecular CT fluorescence emission of PI(BPDA/PDA) film is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 20 publications
3
93
0
Order By: Relevance
“…[1][2][3][4][5] We have already achieved the synthesis of nearly colorless polyimides using dianhydrides with polyalicyclic structures. [6][7][8] Moreover, we reported entirely colorless polyimides prepared from a dianhydride with a bicyclo[2.2.1]heptane structure and aromatic diamines, although it was essential that a mixture of triphenylphosphite and pyridine (TPP/Py) was added during the course of the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] We have already achieved the synthesis of nearly colorless polyimides using dianhydrides with polyalicyclic structures. [6][7][8] Moreover, we reported entirely colorless polyimides prepared from a dianhydride with a bicyclo[2.2.1]heptane structure and aromatic diamines, although it was essential that a mixture of triphenylphosphite and pyridine (TPP/Py) was added during the course of the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…(73, 14) We found that a new absorption band appeared in die longer wavelength region upon blending of PI(BPDA/CHDA) (CHDA: trans 1,4-cyclohexyldiamine) with P1(DMCDA/PDA) (DMCDA: 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride) which are both Pis possessing no CT character as shown in Figure 4. Thus, for the blended PI system an intermolecular donor-acceptor interaction was demonstrated from die results in Figure 4.…”
Section: Results and Discussion Donor-acceptor Alternative Sequence Imentioning
confidence: 92%
“…For several model compounds, the Stern-Volmer analysis were Φ ( (385nm) = kf /(kf + k d + k isc + k CT ) <10" 4 (2)…”
Section: Photochemistry Of Benzophenone-typementioning
confidence: 99%